Slovene students in central and eastern Europe up to 1918 - Gantar Godina, Irena (Dve domovini, 1996)
The article is a survey of so-called temporary emigration of Slovene intellectuals who were, up to 1919, forced to study at non-Slovene universities. The majority attended German universities in Vienna and Graz; after 1882 there was a significant number of students at the Charles University in Prague, while Slovene Catholics tried to persuade Slovene pupils to attend the universities in Galicia, i.e. in Kraków and Lvov. The Slovene intellectuals who voluntarily left to lecture at Russian schools in the 60s and 70s of the 19th century are mentioned as a special phenomenon.
Keywords: 19./20.st.; Central Europe; Eastern Europe; education; izobraževanje; profesorji; slovenski izseljenci; Srednja Evropa; student; študenti; Vzhodna Evropa